Platinum Chemotherapy Induces Lymphangiogenesis in Cancerous and Healthy Tissues That Can be Prevented With Adjuvant Anti-VEGFR3 Therapy - Harris, Alexandra R.; Esparza, Savieay; Azimi, Mohammad S.; Cornelison, Robert; Azar, Francesca N.; Llaneza, Danielle C.; Belanger, Maura; Mathew, Alexander; Tkachenko, Svyatoslav; Perez, Matthew J.; Rosean, Claire Buchta; Bostic, Raegan R.; et al. (Frontiers in Oncology, 2022)
Chemotherapy has been used to inhibit cancer growth for decades, but emerging evidence shows it can affect the tumor stroma unintentionally promoting cancer malignancy. After treatment of primary tumors, remaining drugs drain via lymphatics. Though all drugs interact with the lymphatics, we know little of their impact on them. Here, we show a previously unknown effect of platinums, a widely used class of chemotherapeutics, to directly induce systemic lymphangiogenesis and activation. These changes are dose-dependent, long-lasting, and occur in healthy and cancerous tissue in multiple mouse models of breast cancer. We saw similar effects in human ovarian and breast cancer patients whose treatment regimens included platinums. Carboplatin treatment of healthy mice prior to mammary tumor inoculation increases cancer metastasis as compared to no pre-treatment. These platinum-induced phenomena could be blocked by VEGFR3 inhibition. These findings have implications for cancer patients receiving platinums and may support the inclusion of anti-VEGFR3 therapy into treatment regimens or differential design of treatment regimens to alter these potential effects.